A study on factors of work-life balance affecting employees' job performance at QSR brands (M) Holding Sdn. Bhd. / Farhanim Mohd Paili - Mohd Paili, Farhanim (Faculty of Business And Management, 2016)
The purpose of this study is to identify the level of the factors in work-life balance that affected employees Job Performance in QSR Brands (M) Holding Sdn. Bhd. This study is to determine the level of the factors in work-life balance that affected employees' job performance in the organization and to identify the level of factor in work-life balance and the level employees' job performance in the organization. The data were collected from 56 employees in human resources department, QSR Brands (M) Holding Sdn. Bhd. The data is analyzed by using statistical analysis and using Social Science Software, (SPSS) version 20. Findings are indicated that the level of the factors in work-life balance that affected the employees' job performance in the organization. Some of recommendation was stated in this study to improve level of the factors work-life balance.